Disperse Dyes Based on Thiazole, Their Dyeing Application on Polyester Fiber and Their Antimicrobial Activity - S. K. Zadafiya; J. H. Tailor; G. M. Malik (Journal of Chemistry)
Various diazotized aryl amines were coupled with N-(4-nitrophenyl)-2-[(4-phenyl-1,3-thiazol-2-yl)amino]acetamide to give the corresponding various azo disperse dyes (D1-D13). These dyes were applied to polyester fiber by HTHP method and their fastness properties were evaluated. Dyes were characterized by IR, elemental analysis, and NMR spectral studies. These dyes showed very good antibacterial and antifungal activities.